Analisis Kualitas Lingkungan Fisik Permukiman Kecamatan Pakualaman Kota Yogyakarta - Noor Awanda, Hanifa, Agus Anggoro Sigit, S. Si, M. Sc (2017)
Planning and structuring city is one of the way to improve quality of the settlements environment, that's why the assessment and measuring quality of the settelments environment is needed. The purpose of this research are,1) Knowing quality of the settelments environment distribution at Pakualaman District 2) Knowing the dominant factors that affect quality of the settelments environment at Pakualaman District. This research using Survey Method with Purposive Sampling as the sampling method and analyzing with overlay. Parameter in this research consist of 6 parameters from satellite imagery, settlement building density, settlement pattern, trees, wide driveways, condition of driveway, settlement location and 5 parameters from field consist of the availibility of drinking water, saniton, sewer flooding and rain water and sewage and garbage dumps. This research using survey for validating satellite imagery interpretation and for collecting field parameter data. The results of this research show that the distribution of good class with 14,65 ha area located around Puro Pakualaman, intermediate class with 31,64 ha area located a bit far from main road and bad class with 6,65 ha area located around Sungai Code, near with traditonal market and jail. Flood parameter and the settlement building density are dominant factors that affect the quality of physical settlement environment at Pakualaman District.